Hukuman Terhadap Tindak Pidana Kekerasan dalam Rumah Tangga Menurut Hukum Islam - Risdianto Risdianto (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2021)
Domestic violence is a serious concern of all parties, thus giving birth to Law Number 23 of 2004 concerning the elimination of domestic violence. According to Islam, domestic violence is different from other criminal acts, such as murder, injuring qisahah, theft by cutting off hands, adultery with caning or stoning. The basis for criminal sanctions for domestic violence is not explained in the text (al-Qur'an and Hadith), so the punishment is expressly absent. This study uses a qualitative method that aims to enrich the scientific treasures of Islamic law and input for parties related to legal matters. The research found that domestic violence criminal sanctions are ta'zir punishment determined by the ruler (government), because it is not explained in the al-Qur'an or Hadith, so that its existence is left to the ruler's decision. This punishment (Jarimah) ta'zir is different from other punishments such as murder, adultery, theft and others whose explanation is contained in Islamic law.